ON ONE SCIENTIFICALLY BASED SOWING MANAGEMENT FOR GETTING PARETO-OPTIMAL CROPS HARVEST (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In the present work, we construct and study a mathematical model for one important agrarian problem of grain production, in which it is necessary to obtain such a guaranteed harvest of crops, the yield of which depends on soil-climatic conditions, so that the gross income from the sale of the grown crop is maximum. The constructed mathematical model is a multi-criteria optimization problem (with five criteria), and it can be attributed to optimal control, in which the controlled parameters are the kind and proportion of crops to be sown. Based on the results obtained, a concrete example is implemented using the application package Mathcad, version 14.0.0.163.